CAR T Cell Therapy in Primary Brain Tumors: Current Investigations and the Future - Lin, Ya-Jui; Mashouf, Leila A.; Lim, Michael (Frontiers in Immunology, 2022)
Chimeric antigen receptor T cells (CAR T cells) are engineered cells expressing a chimeric antigen receptor (CAR) against a specific tumor antigen (TA) that allows for the identification and elimination of cancer cells. The remarkable clinical effect seen with CAR T cell therapies against hematological malignancies have attracted interest in developing such therapies for solid tumors, including brain tumors. Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults and is associated with poor prognosis due to its highly aggressive nature. Pediatric brain cancers are similarly aggressive and thus are a major cause of pediatric cancer-related death. CAR T cell therapy represents a promising avenue for therapy against these malignancies. Several specific TAs, such as EGFR/EGFRvIII, IL13R2, B7-H3, and HER2, have been targeted in preclinical studies and clinical trials. Unfortunately, CAR T cells against brain tumors have showed limited efficacy due to TA heterogeneity, difficulty trafficking from blood to tumor sites, and the immunosuppressive tumor microenvironment. Here, we review current CAR T cell approaches in treating cancers, with particular focus on brain cancers. We also describe a novel technique of focused ultrasound controlling the activation of engineered CAR T cells to achieve the safer cell therapies. Finally, we summarize the development of combinational strategies to improve the efficacy and overcome historical limitations of CAR T cell therapy.